6LoWPAN header compresses with end-to-end hybrid route-over using cross-layer and adaptive backoff exponent - Awwad, Samer Adnan Ali Bani (2016)
In the world of Internet of Things (IoT) and wireless embedded internet, the IPv6 over Low-Power Wireless Personal Area Network (6LoWPAN) was specifically introduced to enable IPv6 global internet connectivity for Low-Power Wireless Personal Area Network (LOWPAN). However, this requires the LOWPAN embedded devices to run IPv6 protocol. On the other hand, enabling IPv6 protocol for embedded devices is not directly applicable due to limited IEEE 802.15.4 frame size, huge headers sizes and routing challenges.